2005
DOI: 10.2337/diacare.28.5.1139
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Adiponectin Gene Polymorphism on the Rosiglitazone Response in Patients With Type 2 Diabetes

Abstract: OBJECTIVE -The aim of this study was to examine the effects of rosiglitazone on adiponectin and plasma glucose levels in relation with common adiponectin gene (ACDC) polymorphisms.RESEARCH DESIGN AND METHODS -A total of 166 patients with type 2 diabetes were treated with rosiglitazone (4 mg/day) for 12 weeks without changing any of their previous medications. In all, single nucleotide polymorphism (SNP)45 and SNP276 of ACDC were examined.RESULTS -Regarding SNP45, there was a smaller reduction in the fasting pl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
73
0
9

Year Published

2006
2006
2019
2019

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 99 publications
(87 citation statements)
references
References 24 publications
(24 reference statements)
5
73
0
9
Order By: Relevance
“…Multiple regression results showed that the rs10192566 genetic effect remained signifi cantly associated with rosiglitazone response (defi ned by a greater than 15% decrease in HbA1c levels after 12 weeks) after adjustment for age, gender, initial body weight gain, baseline FPG, and HOMA-IR [odds ratio (OR) 2.21, P = 0.013] ( Table 6). This genetic effect of LPIN1 became stronger when regression analysis included previously reported gene loci (adiponectin and PPAR-c, OR = 3.39, P = 0.004) [9,10].…”
Section: Resultsmentioning
confidence: 79%
See 4 more Smart Citations
“…Multiple regression results showed that the rs10192566 genetic effect remained signifi cantly associated with rosiglitazone response (defi ned by a greater than 15% decrease in HbA1c levels after 12 weeks) after adjustment for age, gender, initial body weight gain, baseline FPG, and HOMA-IR [odds ratio (OR) 2.21, P = 0.013] ( Table 6). This genetic effect of LPIN1 became stronger when regression analysis included previously reported gene loci (adiponectin and PPAR-c, OR = 3.39, P = 0.004) [9,10].…”
Section: Resultsmentioning
confidence: 79%
“…* P-values reflect differences between the CC and CG+GG genotypes assessed by t-test. 9 P-value assessed by chi-square test. Bonferroni correction was made to control the effects of multiple comparisons.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations